Hubungan Lingkungan Fisik Rumah Terhadap Kejadian Tb Paru Di Puskesmas Telaga Dewa Kota Bengkulu Tahun 2023 - Tranado, Hengki; Saputra, Fery Surahman; Hasanudin, Yalta; Habibi, Julius; Sinaga, Maylina Dewi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Globally, in 2016 there were 10.4 million cases of TB incidents, equivalent to 120 cases per 100,000 population. The five countries with the highest incidence of cases in the world are India, Indonesia, China, the Philippines, and Pakistan (Ministry of Health., 2018). In 2017 there were around 558,000 new cases of rifampicin-resistant TB (RR TB). Where almost half of these cases occurred in three countries, namely India (24%), China (13%), and Russia (10%) (Ministry of Health, 2021). In 2018, globally the largest percentage of TB cases occurred in Southeast Asia (44%) and the smallest percentage in Europe (3%). And in 2019, the largest number of TB cases were in Southeast Asia (44%), Africa (25%), and the West Pacific (18%) (WHO., 2020). The methods used in this study were bivariate and multivariate. The results are as follows: 1. The results of the study show that more than half of the respondents 42 (63.6%) have adequate home lighting, more than half of the respondents 37 (56.1%) have adequate home ventilation, more than half of the respondents 40 (60.6%) have adequate home floor types, more than half of the respondents 44 (66.7%) have inadequate home density and more than half of the respondents 39 (59.1%) have adequate home humidity. 2. The results of the study showed that there was a relationship between lighting, ventilation, floor type, residential density and humidity with the incidence of Pulmonary TB at the Telaga Dewa Health Center, Bengkulu City in 2023. 3. The results of the study showed that lighting obtained an OR value of 3.946 (95% CI: 1.343-11.600), lighting obtained an OR value of 3.121 (95% CI: 1.133-8.603), floor type obtained an OR value of 5.041 (95% CI: 1.707-14.890), residential density obtained an OR value of 0.236 (95% CI: 0.077-0.722) and humidity obtained an OR value of 3.200 (95% CI: 1.145-8.944).